Antigenic structure of the flavivirus envelope protein E at the molecular level, using tick-borne encephalitis virus as a model. - Mandl, C W (1989)
A model of the tick-borne encephalitis virus envelope protein E is presented that contains information on the structural organization of this flavivirus protein and correlates epitopes and antigenic domains to defined sequence elements. It thus reveals details of the structural and functional characteristics of the corresponding protein domains. The localization of three antigenic domains (composed of 16 distinct epitopes) within the primary structure was performed by (i) amino-terminal sequencing of three immunoreactive fragments of protein E and (ii) sequencing the protein E-coding regions of seven antigenic variants of tick-borne encephalitis virus that had been selected in the presence of neutralizing monoclonal antibodies directed against the E protein. Further information about variable and conserved regions was obtained by a comparative computer analysis of flavivirus E protein amino acid sequences. The search for potential T-cell determinants revealed at least one sequence compatible with an amphipathic alpha-helix which is conserved in all flaviviruses sequenced so far. By combining these data with those on the location of disulfide bridges (T. Nowak and G. Wengler, Virology 156:127-137, 1987) and the structural characteristics of epitopes, such as dependency on conformation or on intact disulfide bridges or both, a model was established that goes beyond the location of epitopes in the primary sequence and reveals features of the folding of the polypeptide chain, including the generation of discontinuous protein domains.